DESIGN AND PERFORMANCE EVALUATION OF A NOVEL ULTRASONIC WELDING SONOTRODE FOR LANGEVIN TRANSDUCER USING FINITE ELEMENT APPROACH - Mughal, Khurram Hameed; Ahmad, Naseer; Hayat, Nasir; Qureshi, Mohammad Asif Mahmood; Bugvi, Salman Abubakar; Jamil, Muhammad Fawad; Khan, Mohammad Aamir (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Ultrasonic welding (USW) is recognized as a sustainable and green manufacturing process due to its high energy efficiency, cleanliness, and excellent welding attributes. The performance of USW majorly depends on small end vibration amplitude (SEVA), achieved through a sonotrode, whose design has been the focus of many researchers. A high SEVA is essential for achieving excellent welding attributes, minimizing wastage, and ensuring a clean environment. In this study, a novel USW sonotrode was designed to enhance the output amplitude of the Langevin ultrasonic transducer (LUT). The sonotrode was evaluated for eigenfrequency characterization and harmonic excitation response through finite element analysis. The performance of this novel ultrasonic transducer was evaluated in terms of SEVA and various types of stresses at an operating frequency close to but higher than the LUT’s axial modal frequency. Variations in axial displacement and Von Mises (VM), axial, tangential, radial, principal, and shear stresses were examined along the length of the tool for titanium, aluminum, and steel sonotrodes. The SEVA of the aluminum sonotrode was 136.72% and 5.87% higher than that of the titanium and steel sonotrodes, respectively. The equivalent VM stress in the steel sonotrode was 159.2% and 379.2% greater than their aluminum and titanium counterparts. Selected cases from the present study were compared with prior research, revealing a reasonable agreement. This work provides insights into the performance of sonotrodes in USW, offering potential paths for improving the effectiveness of this sustainable manufacturing process.